1995
DOI: 10.1099/13500872-141-10-2553
|View full text |Cite
|
Sign up to set email alerts
|

Poly- -hydroxybutyrate (PHB) biosynthetic genes in Rhizobium meliloti 41

Abstract: Genes encoding fiketothiolase (phaA), acetoacetyl-CoA reductase (phaB) and PHB-synthase (phaC) from R. meliloti 41, together with a fourth gene, referred to as ORF1, presumed to be involved in PHB biosynthesis, have been cloned and sequenced. phaA, phaB and ORFl were identified by heterologous hybridization on a cosmid library, while phaC was isolated by cloning the transposon-tagged fragment from a R. meliloti PHB-Tn5 mutant. phaA and phaB were functionally expressed in Escherichia coli while phaC was able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 42 publications
1
44
0
Order By: Relevance
“…Most members of the SDR family of enzymes are NAD(P)-dependent oxidoreductases of 250 to 300 amino acids that contain no metal cofactors and have a wide range of substrate specificities that include alcohols, sugars, prostaglandins, and hydroxysteroids (19,20,34). BadH is most similar to eubacterial acetoacetyl-CoA reductases involved in polyhydroxyalkanoate and fatty acid biosynthesis (about 40% amino acid identity) (36,43). It is 37% identical to 7␣-hydroxysteroid dehydrogenase from E. coli and 36% identical to 20␤-hydroxysteroid dehydrogenase from Streptomyces exfoliatus.…”
Section: Resultsmentioning
confidence: 99%
“…Most members of the SDR family of enzymes are NAD(P)-dependent oxidoreductases of 250 to 300 amino acids that contain no metal cofactors and have a wide range of substrate specificities that include alcohols, sugars, prostaglandins, and hydroxysteroids (19,20,34). BadH is most similar to eubacterial acetoacetyl-CoA reductases involved in polyhydroxyalkanoate and fatty acid biosynthesis (about 40% amino acid identity) (36,43). It is 37% identical to 7␣-hydroxysteroid dehydrogenase from E. coli and 36% identical to 20␤-hydroxysteroid dehydrogenase from Streptomyces exfoliatus.…”
Section: Resultsmentioning
confidence: 99%
“…The aniA gene is located upstream of phaAB in the opposite orientation (34,46). They demonstrated that aniA is inducible under anaerobic conditions but that the defect of aniA causes little effect on P(3HB) synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…(GenBank accession no. U78047), Methylobacterium extorquens (Valentin & Steinbu$ chel, 1993), Paracoccus denitrificans (Ueda et al, 1996), Pseudomonas aeruginosa (Timm & Steinbu$ chel, 1992) (containing two phaC genes), P. oleovorans (Huisman et al, 1991) (containing two phaC genes), Rhizobium etli (Cevallos et al, 1996), Rhizobium meliloti (Tombolini et al, 1995) and Zoogloea ramigera (GenBank accession no. U66242).…”
Section: Methodsmentioning
confidence: 99%